Educational Institutions and Religious Identity Polarization: Toward an Educational Anti-Polarization Framework - Suwardi; Abdurrahman R. Mala; Tuharso; Hasyim Mahmud Wantu; Firman Sidik; Nur Gamar; Najamuddin Petta Solong (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Religious identity polarization has become an increasingly significant challenge for social cohesion in pluralistic societies. Educational institutions are frequently regarded as strategic spaces for fostering tolerance, promoting intergroup understanding, and preventing the development of exclusionary identities. This study aimed to systematically examine the role of educational institutions in preventing religious identity polarization and to identify the contextual conditions that support the effectiveness of such efforts. A systematic literature review was conducted following the PRISMA framework. Literature searches were performed across Scopus, Web of Science, Google Scholar, and SINTA databases, focusing on studies published between 2019 and 2025. From an initial pool of 284 records, 31 studies met the inclusion criteria and were analyzed using thematic analysis. The findings revealed four interconnected educational mechanisms that contribute to preventing religious identity polarization: inclusive curricula, dialogical pedagogical approaches, heterogeneous educational environments, and digital media literacy. The review also identified five key conditions that enhance effectiveness, namely institutional leadership commitment, educator capacity, policy consistency, family and community involvement, and evidence-based program implementation. Drawing upon Social Identity Theory, Intergroup Contact Theory, Social Capital Theory, and digital polarization perspectives, the study proposes an Educational Anti-Polarization Framework that conceptualizes educational institutions as multilevel systems shaping cognitive, social, pedagogical, and digital dimensions of identity formation. The findings highlight the importance of integrated educational strategies for strengthening social cohesion and fostering inclusive citizenship in increasingly diverse and digitally connected societies.